2008
DOI: 10.4012/dmj.27.415
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Biocompatibility of Acid-etched Titanium

Abstract: The purpose of this study was to evaluate the effects of acid-etched titanium on the biological responses of osteoblast-like MC3T3-E1 cells. Four types of treatments (polishing, sandblasting, concentrated H2SO4 etching, and concentrated H2SO4 etching with vacuum firing) were carried out on the surfaces of commercially pure titanium (cpTi) disks. MC3T3-E1 cells were then cultured on the treated cpTi surfaces. Through surface roughness measurement and SEM analysis, it was found that the acid-etched surfaces show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 37 publications
3
56
1
Order By: Relevance
“…Our data are also in agreement with findings showing that acid etching of grit blasted titanium had no substantial impact on proliferation and collagen production of MC3T3-E1 cells 22) or on osteogenic differentiation of MG63 cells 21) . Thus, the present results provide additional support for the view that modifications of already grit blasted surfaces, even if they might have an impact on the process of osseointegration in vivo, do not necessarily have an impact on cell behavior in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…Our data are also in agreement with findings showing that acid etching of grit blasted titanium had no substantial impact on proliferation and collagen production of MC3T3-E1 cells 22) or on osteogenic differentiation of MG63 cells 21) . Thus, the present results provide additional support for the view that modifications of already grit blasted surfaces, even if they might have an impact on the process of osseointegration in vivo, do not necessarily have an impact on cell behavior in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…Microspheres of diameter in the range 10-540 µm are typically accelerated toward the surface to be treated, using a compressed air or nitrogen blow. Most used grid materials include corundum (Al 2 O 3 ) [9,10], silicon carbide (SiC) [11], titania (TiO 2 ) [12], hydroxyapatite (HA) [13], zirconia (ZrO 2 ) [14], silica (SiO 2 ) [15] and aluminum powders [15]. The main effect of sandblasting is to change the morphology of the treated surface, substantially increasing its roughness.…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…Several studies have reported that acid treatment modifies the wettability of titanium surfaces [13,23]. In wettability test, the contact angle of acid treatment was significantly higher than non-treated and alkali treatment.…”
Section: -2 Corrosion Depthmentioning
confidence: 94%
“…Chemical treatments corrode the titanium surface, making it rough, extremely hydrophilic, and suitable for bone formation [23]. The corrosion depth is not a serious problem for solid titanium materials such as implant fixtures.…”
Section: Introductionmentioning
confidence: 99%